Validation of vital sign measurement by nanosecond pulse near-field sensing and the conductive silver paste printed textile technique. Issue 1 (January 2023) - Chen, Kuan-Hung; Chen, Yong-Syuan; Chen, Chih-Lung; Yang, Ching-Yi; Yang, Chiau-ling; Yang, Fu-Cheng; Liu, Chia-Hao; Huang, Shu-Chun
Vital sign monitoring is fundamental in daily patient care. Wearable technology has become an important tool in personalized medicine; however, there is a tradeoff problem between accuracy and comfort caused by the elastic textile used. Our study sought to examine the accuracy of heart rate (HR) and breathing rate (BR) monitoring as measured by iSmartweaR, a novel wearable and wireless sensor that uses the laser Doppler technique, with special focus on sex and different static postures. A total of 30 male and 23 female patients, including 23 patients with cardiovascular diseases and 30 healthy participants, were recruited. The HR and BR were measured with iSmartweaR and the gold standard method (CardioSoft and MasterScreen™ CPX) simultaneously in three static postures (supine rest, right lateral decubitus, and left lateral decubitus). The mean errors of HR and BR between iSmartweaR and the gold standard method were close to zero (0.55 and 0.71, respectively). The standard deviations of the HR error and BR error were 0.59 and 0.67, respectively. Disease, posture, sex, and measurement time did not cause clinically significant measurement errors. The overall percentage of missing data was 7.01%. The use of iSmartweaR was valid across different sexes and static postures. It is real-time, continuous and manpower-saving, and can be applied in patient care.